Analysis of variables in the design of pillars underground mining support - Ortiz Sánchez, Oswaldo (2013)
Reliable pillar design is of great importance for low cost and safe underground mining support for long periods of time in under ground exploitation.This study analyses pillar variables which have a bearing on underground pillar resistance and stress generation. Two dimensional models were prepared and tested simulating underground mining excavations supported by pillars. Laboratory tests were performedon transparent doubly refracting plates tested in the field of a plane polarized light of a polariscope. On compression the plategenerates fringes of many orders which have values in terms of shear. The level of importance of each variable is obtained bycorrelation and regression analysis of the data. Values of the pillar stress was generated as a function of each of the independentvariables and also as a function of the inter relationships of independent variables and the influence of each of these variables onthe dependent variable. Two analytical models were obtained. These expressions can be used in underground mining pillar design.